Efektifitas Self-Branding Melalui Instagram Pada Generasi Z - Ekayulisa, Ekayulisa Ekayulisa; Maula, Risa Nikmatul; Fannan, Muhammad Rasyid (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Y, 2023)
Social media is a link in distributing information quickly so that it is needed by many people. The aim of this research is to determine the effectiveness of self-branding via Instagram in generation Z, how self-branding works, and generation Z social media which is managed with self-branding so that the effectiveness of self-branding can be known by the wider community, to find out the best way to utilize self-branding through Instagram in generation Z, and knowing that generation Z's social media is managed with self-branding. This research uses a descriptive quantitative method by distributing a questionnaire containing statements related to aspects of self-branding which are filled in by Generation Z Instagram users and use self-branding when playing Instagram. The questionnaire contains statements about aspects of self-branding, the first of which is the competency and ability aspect, showing that respondents agree that the competency and ability aspects can form self-branding through Instagram social media. Competencies and abilities are very diverse, including values, non-academic academic abilities, communication, as well as skills and qualities to gain the trust of society. The second aspect is style, the research results show that respondents agree that the style aspect of each individual is able to form self-branding through Instagram. The purpose of one's own style is to be able to be remembered by other people in socializing and to show the uniqueness that exists in each individual. The third aspect is standards, research results show that each individual has their own self-branding standards, one of which is when they respond to and receive comments from other Instagram social media users. Standards also determine the quality of Instagram users in assessing other people.